A relação entre professor e aluno no Ensino Superior vista por meio da reprovação - Cury, Daniel Gonçalves (2012)
Reprobation, resulting from failure in the course of certain subject, be it by grade and/or absence of the student, has commonly as responsible the student or the master. From a perspective which takes into consideration the importance of social relations for the constitution of subjects, the current research has based upon the Historical-Cultural Psychology and focused on the higher education, having as main objective to understand the relations between masters and students through reprobation, with a view to understand the reality which involves this pair in this context and investigate their influence on the professional formation during graduation. Five students from the Federal University of Uberlândia (UFU) were interviewed, two from the area of Social Sciences, two from Exact Sciences and one from Biological Science, and five students from the same university, being two from Exact Sciences, two from Biological Sciences and one from Social Sciences. For data building open interviews, recorded in audio were used, with a question referring to reprobation, which werer later transcripted and transcreated. Data were analysed through content analysis. Three categories were created: a) Student´s education, in which aspects related to graduation courses were approached, such as the relation of the students with the subjects in which were reproved, the insatisfaction concerning evaluation and teaching methodology, absences during the semester and the meanings attributed to reprobation; b) The relation between masters and students concerning the teaching-learning processes, complying aspects related to limits, distancing and possibilities of approximations existing in this relation, the characteristics of the masters considered to be good mediators, considerations about the responsibility for academical failure and reflexions about the feelings of impotence from the student before the master´s authority; c) The master´s education in the higher education, in which some considerations were commented about such process and detailed reflexions about the existence of gaps in the initial education of the master, as well as a presentation of the need for School Psychology in this phase of the graduation. With this investigation it is possible to infer that pedagogical mediation offered by the master compose one of the solid bases for the teaching-learning process and that, besides, the educational situation is constituted by affective questions which directly influence learning. All these dimensions end up to reflect in the ways that the student relate to the subject content, the master and his own learning. Finally, one reafirms the necessity of the presence of School Psychology in the search for proposals which colaborate to professional formation as well as the proposition of continual courses for the master, benefiting a teaching-learning process process whose objective may be intelectual enhancement of everyone involved.